THE MEANING OF OFFSPRING AND THE SPOUSE SELECTION OF JAVANESE MUSLIMS IN SURABAYA BASED ON MAQASID SHARIAH - Sabri, Fahruddin Ali (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This article aims to examine the significance of offspring ancestry and the spouse selection for Javanese Muslims in Surabaya in particular how social and religious norms influence individual decisions regarding marriage. Javanese Muslim society has binding social norms for its adherents in marriage. This study uses an experimental ethnographic approach with interactive dialogue methods and participant observation for seven months. The findings of the study show that Javanese Muslims in Surabaya still emphasize that offspring in marriage with children is considered a valuable asset of the family and the existence of a household. The absence of children can be considered a disgrace that causes social stigma for spouses. In addition, Javanese Muslims consider it important to the spouse selection with the guidance of the norm of ‘bibit-bebet-bobot’ which involves consideration of offspring, social status, and character of the partner. Although individuals have the freedom to spouses selection, they are bound by social norms to adhere to them to avoid social conflicts and negative stigmas. Social norms that are practiced excessively or negligently cause harm to individuals in spouse selection, this is considered contrary to the principle of middle position in maqasid shariah. The implications of these findings suggest that social norms and constructions in Javanese Muslims are still strong and influence individual decisions in marriage. This study contributes to an understanding of how religious and social norms can shape cultural practices at the local level as well as their relevance in the context of Islamic and social norms.